Myocardial Ischemia Detection from Slope of ECG ST Segment (Bangladesh Journal of Medical Physics, 2018)
Myocardial ischemia occurs when blood flow to heart is reduced preventing it from receiving enough oxygen. It is a possible indication of partial or complete blockage of coronary arteries. Though ischemia is accompanied by symptoms (fatigue, chest pain, shortness of breath etc.) sometimes it can be silent. If not treated, it can lead to various heart diseases. Most importantly it can progress to myocardial infarction (heart attack), which can be fatal. Thus detecting ischemia at an early stage is important to prevent serious implications. Nowadays personal healthcare monitoring systems are used which provide vital physiological information. In future ECG measurement devices would also be common in homes. So, the proposed work intends to develop an algorithm in detecting myocardial ischemia from ECG, which would be computationally less complex and easy to implement in homecare ECG devices. One way to do it is through continuous or long term monitoring of ECG. The ST segment elevation (or depression) indicates presence of ischemia. The proposed method measures slope of ST segment which must vary in case of ST changes. The algorithm is tested on selected records of the European ST-T database and returns an accuracy of 83.33%.Bangladesh Journal of Medical Physics Vol.10 No.1 2017 12-24